Pindar's poetry, patrons, and festivals : from archaic Greece to the Roman Empire - Hornblower, Simon; Morgan, Catherine, 1961- (Oxford University Press, 2007)
A collection of essays, by a stellar team of authors, about the praise (`epinikian') poetry of the classical poets Pindar and Bacchylides. The social and physical, as well as the literary, background to these poems celebrating athletic victory is explored in light of the latest archaeological and sociological insights.